Penguatan Komunikasi Antar Budaya Melalui Parade Budaya di Kalangan Mahasiswa di Universitas PGRI Kanjuruhan Malang - Nofiana Paskalia Letek; Engelbertus Kukuh Widijatmoko; Iskandar Ladamay (International Forum of Researchers and Lecturers, 2024)
PGRI Kanjuruhan University Malang's ethnically diverse student body often has challenges or barriers while attempting to communicate with individuals from other cultural backgrounds, according to the researcher's observations. Finding out what intercultural communication is, painting a picture of it, and making an attempt to foster more intercultural communication among PGRI Kanjuruhan University students in Malang are the objectives of this study. A qualitative descriptive type and technique are used in this study. information gathered via documentation, observation, and interviews. Intercultural communication is defined as a communication activity that takes place between communication participants that have distinct cultural origins, based on the study findings from the initial issue formulation. However, it is possible to infer from the second phrasing of the issue that the students at PGRI Kanjuruhan University, Malang, exhibit a picture of intercultural communication. Thus far, intercultural communication has gone well since everyone on our multicultural campus can interact and talk with people from various cultural backgrounds. from Papua, Maluku, NTT, Sumatra, Java, and Kalimantan. To improve intercultural communication among students at PGRI Kanjuruhan University Malang, specifically through cultural parade activities in addition to cultural seminar activities, sports activities, and student activity units, can be concluded based on the research results from the third problem formulation. Students and aspiring researchers may submit suggestions to PGRI Kanjuruhan University Malang.